Strong gene flow explains lack of mating system variation in the perennial herb, Vincetoxicum hirundinaria, in a fragmented landscape - Muola Anne; Scheepens Johannes F.; Laukkanen Liisa; Kalske Aino; Mutikainen Pia; Leimu Roosa (WILEY, 2022)
Fragmented landscapes may have implications for the genetic structure of populations and for the microevolution of plant species. In particular, landscape fragmentation and/or population isolation might affect the evolution of plant mating systems. Here, we study the consequences of landscape fragmentation on the genetic structure of populations of a perennial herb, Vincetoxicum hirundinaria with a mixed mating system. Our study area, the south-western Finnish archipelago, was formed after the glacial ice sheet started to retreat 12 000 years ago. Due to the isostatic land uplift following the glacial retreat, suitable habitats have been formed gradually, and as a consequence, populations of V. hirundinaria differ in age, size and their degree of isolation in the area. We hypothesized that a mixed-mating system has been selected for in these populations due to the advantage of self-fertilization in newly colonized areas and the advantage of outcrossing in adaptation to heterogeneous environments. To test this hypothesis, we collected seeds of open-pollinated flowers from 13 V. hirundinaria populations differing in size, age and isolation, and used 15 microsatellite markers to perform progeny-array analysis to estimate population-level outcrossing rates, population genetic indices and population structure. We found that V. hirundinaria is almost completely outcrossing in the study area with no signs of past self-fertilization and/or mating among relatives. The overall low inbreeding coefficients indicate that even in small populations mating among relatives is rare. High allelic richness of both maternal and offspring genotypes as well as limited genetic differentiation among the studied populations indicate strong gene flow among them. Our findings suggest that V. hirundinaria has successful seed and pollen dispersal among populations that has allowed colonization of new habitats in this fragmented landscape and led to a genetically well-mixed group of populations at the scale of the study.